Anxiety and need for support of college students during the SARS-CoV-2 pandemic: An exploratory study. (13th April 2021) - Torres, A.; Melo, R.; Príncipe, F.; Ferreira, A.; Quesado, A.
Abstract : Introduction: During the pandemic state, college students are exposed to additional stressful factors, including but not limited to: fear of being infected; fear of infecting a significant person; deal with a new reality of economic uncertainty; challenges of distance education; new rules in face-to-face classes; restrictions on access to internships and higher demanding in internships. Objectives: This exploratory study aims to assess levels of anxiety and the perception of the need for support of students of a Portuguese Higher Education Institution (HEI). Methods: An exploratory study was developed, on the return of students to the presential classes after the academic lockdown. It was spread out an email for all students with a link for an online form, which includes sociodemographic questions, a screening question of the anxiety level, and the need for support level (rating scales 0-10). Results: It was obtained 36 answers from mostly female students (92%) with 17 to 21 years old (67%). Answers present an average anxiety level of 5.4 (Min=1; Max=9; SD=2.23), with 58% of answers with a score of anxiety level of 5 or higher. The need for support average was 3.7 (Min=1; Max=9; SD=2.23), with 33% of answers with a score of 5 or higher. Conclusions: It is necessary to continuously monitor the anxiety level and the need for support of college students during the SARS-Cov-2 pandemic. It is similarly relevant to have responses of HEI to promote mental health and to answer to the high levels of students' anxiety and needs for support during the pandemic.